Visualizing Vibrancy: A Multimodal Analysis of Photographic Representations in Ho Chi Minh City Travel Guidebook - Le Minh Phuoc Ta; Thi Nhu Ngoc Nguyen (LACULTOUR: Journal of Language and Cultural Tourism, 2026)
This study investigates the meaning-making process of 224 photographic representations in Ho Chi Minh City Travel Guidebook (English e-version) in relation to its tourism slogan Vibrant Ho Chi Minh. The research adopts a multimodal discourse analysis approach, integrating both qualitative and quantitative methods. The primary theoretical framework is adapted from Hunter’s (2008) typology of photographic representations, which was, in turn, developed from Kress and Van Leeuwen's (2006) Visual Grammar. The findings indicate that the vibrancy of Ho Chi Minh City, Vietnam is significantly emphasized by these photographic representations, with its rich cultural aspects (51.79%) and modern infrastructure (20.98%) being prominently depicted together with its outstanding tourism products (21.87%). In other words, this vibrancy is constructed from both internal vibrancy (intangible values) and external vibrancy (tangible infrastructure and amenities). Furthermore, in the context of Vietnam’s robust tourism development and the globalizing trends within the industry, the study proposes recommendations aimed at enhancing the persuasive efficacy of the photographic representations in tourism texts promoting destinations in Vietnam.